Peran dan Tanggung Jawab PPAT terhadap Pendaftaran Hak Atas Tanah dalam Proses Penerbitan Sertifikat Tanah Secara Elektronik - Mutia Kanza; M. Sudirman; Benny Djaja (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2024)
PPAT plays a significant role in promoting digital transformation in the land administration sector and in supporting the successful implementation of electronic land certificates in Indonesia. Within this system, the PPAT holds a highly strategic position because the deeds they issue serve as the legal basis for registering land rights in the electronic certificate issuance process.This study aims to examine the roles and responsibilities of PPATs in the registration of land rights within the electronic certification system. The research employs a normative juridical method by reviewing statutory regulations, legal literature, and policies related to the digitalization of land services The findings indicate that PPATs are responsible for accurately collecting data, applying valid digital signatures and completing and uploading electronic information in accordance with the established procedures, thereby ensuring legal certainty and the integrity of land-related transactions. Their responsibilities encompass administrative, legal, and ethical dimensions, including ensuring the completeness and accuracy of documents, validating the authenticity of deeds, safeguarding the rights of involved parties, and supporting government policies on land rights registration.